Human rights in China a social practice in the shadows of authoritarianism - Pils, Eva (Cambridge, UK Malden, MA Polity, 2018)
"How can we make sense of human rights in China's authoritarian system? In this insightful book, China law expert Eva Pils offers a nuanced account of this contentious area, examining human rights as a set of social practices involving a variety of actors, including officials of the system and civil society actors. Drawing on a wide range of resources including years of interaction with Chinese human rights defenders, Pils discusses sources of human rights violations, as well as institutional avenues of protection and social practices of human rights defence. Three central areas are given special attention: liberty and integrity of the person and the right not to be tortured; freedom of thought and expression; and inequality and socio-economic rights. Pils argues that the Party-State system is inherently opposed to human rights principles in all these areas. Yet, civil society actors have developed social practices of human rights advocacy whose political significance is not entirely dependent on the Party-State. Despite authoritarianism's lengthening shadows, China's human rights movement has so far proved resourceful and resilient, and the trajectories discussed in this book will continue to shape ongoing struggles"--Provided by publisher.
Machine generated contents note: Map Chronology Acknowledgements List of Abbreviations Introduction 1. Human Rights and Competing Conceptions of Justice, Law and Power in China 2. Institutional Avenues of Human Rights Advocacy 3. Liberty and Life 4. Expression and Thought 5. Inequality and Socio-economic Rights 6. Rights Defenders Conclusion Notes.
Includes bibliographical references (pages [153]-214) and index.
Keywords: Human rights -- China; Human rights advocacy -- China; Human rights movements -- China; Authoritarianism -- China